Synthesis of mechanically durable superhydrophobic polymer materials with roughness-regeneration performance. (June 2020) - Liu, Maolin; Luo, Yuanfang; Jia, Demin
Graphical abstract: A robust superhydrophobic polymer material with roughness-regenerative characteristics is fabricated for against multi-cycle mechanical damages (>250 cycles). Highlights: A superhydrophobic material based on polyurethane and silica is proposed. The polymeric material exhibits robustness upon mechanical damage. The superhydrophobic material possesses roughness-regenerative feature. The polymeric material presents repairable performance via sanding treatment. Abstract: Although superhydrophobic materials play important roles in emerging fields because of their anti-wetting behavior, they still face a series of challenges such as brittle rough structure. Herein, a mechanically durable superhydrophobic polymer material (SPM) with roughness-regenerative characteristics was synthesized by integrating acrylate-terminated polyurethane (A-PU) with precipitated silica particle (PSP) using vinyltriethoxysilane (VTES) as a bridge. With the optimization of UV curable components, the appropriate covalently cross-linking networks and hierarchical rough structure were formed in the polymer skeleton, endowing the SPM with solid mechanical strength (B hardness) and superior superhydrophobicity (CA > 152°, SA < 5°). Taking advantage of the roughness-regenerative characteristics across the material bulk, the SPM was capable of surviving after multi-cycle abrasion damages (>250 cycles). More importantly, the roughness-regenerative characteristics enabled the damaged SPM to repair its superhydrophobicity via sanding treatment (>40 cycles). Our findings convincingly propose a feasible approach to fabricate versatile superhydrophobic materials as promising candidates for emerging fields.